Comparison of the novel START vascular stiffness index with the CAVI index, assessment of their values and correlations with clinical parameters - I. A. Vasyutin; K. Leon; T. A. Safronova; I. B. Bakholdin; V. S. Barkan; V. A. Milyagin; T. P. Pronko; A. V. Talov; D. E. Tentyukov; V. S. Chulkov; K. V. Peskov; V. I. Podzolkov; et al. (Российский кардиологический журнал, 2023)
Aim. To compare the cardio-ankle vascular index (CAVI) and the novel START vascular stiffness index and assess their values and correlations with clinical parameters.Material and methods. This multicenter study included 928 (403 men and 525 women) randomly selected patients, aged 18 to 89 years (mean age, 41±15,8 years). Inclusion criteria were age over 18 years. There were following exclusion criteria: mental disorder, severe somatic diseases and cancer, contraindications for volume sphygmography using the Fukuda Denshi VS-1500 VaSera system, no patient consent, ankle-brachial index <1,0 and >1,3. Further, according to the main parameters obtained using volum sphygmography, a novel START index was calculated. Comparison of index values and analysis of their correlation with clinical indicators, such as age, systolic blood pressure, diastolic blood pressure, pulse pressure (PP), body mass index and heart rate (HR), were carried out using simple and multiple linear regression, dispersion analysis, calculation of the Pearson coefficient (r), in the software environment R version 4.0.2.Results. Statistical analysis revealed a high correlation between START and CAVI indices (r=0,986, p<0,001). The values of both indices increase significantly with age (ANOVA p><0,001). Both START and CAVI correlate with all studied clinical parameters. However, in men, there was no relationship of the indices with PP and HR (p>0,05). According to multiple linear regression, the relationship between diastolic blood pressure at the age of 30-60 years and PP at the age of 18-40 years with the START index is more pronounced than with the CAVI index. However, further study of the mathematical model did not reveal a significant difference in the index values for groups with and without high blood pressure.Conclusion. The START vascular stiffness index significantly correlates with the CAVI index, showing no significant differences from CAVI in quantitative relationships with blood pressure, body mass index, heart rate, and sex in various subgroups of the subjects.